Amalgamations and the introduction of a statutory merger in the new companies act 71 of 2008: an analysis of the procedure and remedies brought about by the inclusion of these two concepts - Chetty, Nasholan (Centre for Law and Society, 2026)
The introduction of the new Companies Act 71 of2008 has brought about many reforms and regulations to assist present and soon to be incorporated companies. The legislature's sole aim is to provide a functioning stable economic environment for companies in South Africa whilst providing adequate security and remedies for all shareholders and stakeholders. The new Companies Act establishes a, Companies and Intellectual Property Commission as well as a Takeover Regulation panel to ensure that the requirements of the Act are administered correctly.